2021
DOI: 10.1016/j.sjbs.2021.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Grain yield and correlated traits of bread wheat lines: Implications for yield improvement

Abstract: Global wheat yields are suffering due to differences in regional climatic conditions and soil fertility. Plant breeders are continuously working to improve the yield per unit area of wheat crop through selecting superior lines as parents. The screening and field evaluation of available lines allow the selection of superior ones and subsequently improved varieties. Therefore, heritable distinctions among 33 bread wheat lines for yield and related attributes were assessed under field conditions. The experiment i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 42 publications
(51 reference statements)
5
22
0
Order By: Relevance
“…The substantial genetic variation among the genotypes suggests that they exhibit genetic diversity, providing an excellent opportunity for breeders to select suitable genotypes for specific traits of interest in variety development. A similar results reported by Getachew, Ullah and Yared et al [14][15][16] that the analysis of variance revealed significant genetic variability among all traits for the treatments. Table 3 presents the estimated range, minimum and maximum values, along with their corresponding genotypes, mean values, and corresponding standard errors for the nine traits examined in wheat genotypes.…”
Section: Resultssupporting
confidence: 88%
“…The substantial genetic variation among the genotypes suggests that they exhibit genetic diversity, providing an excellent opportunity for breeders to select suitable genotypes for specific traits of interest in variety development. A similar results reported by Getachew, Ullah and Yared et al [14][15][16] that the analysis of variance revealed significant genetic variability among all traits for the treatments. Table 3 presents the estimated range, minimum and maximum values, along with their corresponding genotypes, mean values, and corresponding standard errors for the nine traits examined in wheat genotypes.…”
Section: Resultssupporting
confidence: 88%
“…The properties considered by the millers are mainly kernel weight, hardness, colour, grain protein, and test weight (weight per volume) which are related to grain yield and quality with varying heritability (Aydin et al, 2010;Guzmań et al, 2016;Irfan Ullah et al, 2021). Grain hardness is another essential characteristic for millers.…”
Section: Introductionmentioning
confidence: 99%
“…Drought stress is one of the mainly abiotic stresses negatively affecting the productivity of wheat and regional and landscape scales [19][20][21]. A significant decline in the yield [21][22][23] and related traits of wheat crop has been reported due to drought stress at different phenological stages [11,24,25]. However, the extent of yield reduction depends on the phenological stage of wheat crop and reproductive stage is regarded as the most crucial stage where optimum moisture supply is mandatory for higher yield [5,11,24].…”
Section: Introductionmentioning
confidence: 99%